Correspondence therapy for stuttering - PD, Manohar; M, Jayaram; Rangasayee; Narendiran (Journal of All India Institute of Speech and Hearing)
Behaviour modification can be brought about directly by face to face contact or indirectly through correspondence. Correspondence therapy can be defined as the therapy/treatment carried out through postal correspondence. Correspondence therapy has a place in speech therapeutics where we can effectively use it with stuttering, misarticulation, education of the deaf, etc. Correspondence therapy can be carried out only with certain problems and situations where it does not require sophisticated equipment or skill on the part of the case